Forage yield potential of Sudan grass-cowpea irrigated mixtures in central Sudan - M.M. A1-Bakri, Abdul-Nasser; S. Ibrahim, Abu Elhassan; S. Gangi, Ali (Gezira Journal of Agricultural Science, 2021)
The study was conducted at the Gezira University Farm, Wad Medani, Sudan, during the winter of 1998 and autumn of 1999 to investigate the effects of nine cropping systems, two rates of nitrogen and two harvesting dates on the quantity and quality of the forage produced by Sudan grass-cowpea mixtures. In both seasons, Sudan grass in around two months from sowing while cowpea flowered in about one month. Black seeded Sudan grass variety (SG2) outperformed the light brown seeded Sudan grass variety (SGI). The autumn forage yields were higher than those of winter. Mixing increased the per plant growth parameters of both crops and across seasons. In winter, the fresh forage yield of pure cowpea and the highest yielding mixture (40 SG2 + 20 CP) were comparable (averaging 6.6 t/ha), while in autumn, the highest yielding crop mixture was 30 SG2 + 30 CP (19.01 t/ha) which is not siB1ificantly different from that of pure SG2 (19.08 t/ha). The land equivalent ratio (LER) values exceeded 1.00, in both seasons, showing a clear advantage of mixtures over monocultures. The addition of 44 kg N/ha significantly increased the growth parameters and forage yield of sole Sudan grass and its mixtures with cowpea but not that of pure cowpea. Harvesting at 60 days from sowing appreciably increased growth parameters, fresh forage yield and quality of forage produced by all seeding combinations. Mixing showed significant effects on crude protein percentage, crude fibre percentage, total crude protein and total crude fibre.